Research Pengaruh Literasi Keuangan Dan Mindset Berwirausaha Terhadap Komitmen Organisasi: abstact - Sina, Peter; Manane, Desmon Redikson (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2020)
The purpose of this research was to examine the impact of financial literacy and enterpreneurial mindset on organization commitment. The respondents used were 21 respondents. By using the regression analysis, the results obtained show that financial literacy and enterpreneurial mindset had an influence on organization commitment. Therefore, it is necessary for the organizations to increase the two factors mentioned. Relating to suggestions for future research, it is necessary to add more specify factors on the dimension of organization commitment.